Impaired IgA class switching in APRIL-deficient mice - Castigli, Emanuela (National Academy of Sciences, 2004)
The tumor necrosis factor (TNF) family member APRIL binds to the receptors BCMA on B cells and TACI on B and T cells. To investigate the role of APRIL in immunity, we generated APRIL-deficient mice. APRIL(-/-) mice have normal T and B lymphocyte development, normal T and B cell proliferation in vitro, but increased numbers of CD44(hi)CD62L(lo) CD4(+) effector/memory T cells and increased IgG responses to T-dependent antigens. Serum IgA levels were significantly decreased, and serum IgA antibody responses to mucosal immunization with TD antigens and to type 1 T-independent antigens were impaired in APRIL(-/-) mice. APRIL by itself induced IgA as well as IgG1 isotype switching in CD40-deficient IgM(+)IgD(+) sorted B cells. These results suggest that APRIL down-regulates T cell-dependent antibody responses and promotes IgA class switching.